Proteomic Identification of S-Nitrosylated Proteins in Arabidopsis - Lindermayr, Christian (American Society of Plant Biologists, 2005)
Although nitric oxide (NO) has grown into a key signaling molecule in plants during the last few years, less is known about how NO regulates different events in plants. Analyses of NO-dependent processes in animal systems have demonstrated protein S-nitrosylation of cysteine (Cys) residues to be one of the dominant regulation mechanisms for many animal proteins. For plants, the principle of S-nitrosylation remained to be elucidated. We generated S-nitrosothiols by treating extracts from Arabidopsis (Arabidopsis thaliana) cell suspension cultures with the NO-donor S-nitrosoglutathione. Furthermore, Arabidopsis plants were treated with gaseous NO to analyze whether S-nitrosylation can occur in the specific redox environment of a plant cell in vivo. S-Nitrosylated proteins were detected by a biotin switch method, converting S-nitrosylated Cys to biotinylated Cys. Biotin-labeled proteins were purified and analyzed using nano liquid chromatography in combination with mass spectrometry. We identified 63 proteins from cell cultures and 52 proteins from leaves that represent candidates for S-nitrosylation, including stress-related, redox-related, signaling/regulating, cytoskeleton, and metabolic proteins. Strikingly, many of these proteins have been identified previously as targets of S-nitrosylation in animals. At the enzymatic level, a case study demonstrated NO-dependent reversible inhibition of plant glyceraldehyde-3-phosphate dehydrogenase, suggesting that this enzyme could be affected by S-nitrosylation. The results of this work are the starting point for further investigation to get insight into signaling pathways and other cellular processes regulated by protein S-nitrosylation in plants.